The Tick-Borne Diseases STING study: Real-time PCR analysis of three emerging tick-borne pathogens in ticks that have bitten humans in different regions of Sweden and the Aland islands, Finland. Issue 1 (1st January 2019) - Cronhjort, Samuel; Wilhelmsson, Peter; Karlsson, Linda; Thelaus, Johanna; Sjödin, Andreas; Pawełczyk, Olga; Forsberg, Pia; Lindgren, Per-Eric
ABSTRACT: A milder climate has during the last decade contributed to an increased density and spreading of ixodid ticks, thus enhancing their role as emerging vectors for pathogenic microorganisms in northern Europe. It remains unclear if they contribute to the occurrence of infections caused by the bacteria Bartonella spp., Francisella tularensis subspecies holarctica and the parasite Toxoplasma gondii in Sweden and on the Åland islands, Finland. In this study, we want to improve understanding of the tick-borne transmission of these pathogens. Volunteers were recruited at primary healthcare centers. Ticks and blood samples were acquired from participants recruited in 2008 and 2009. Health questionnaires were completed, and medical records were acquired where applicable. Feeding time was estimated and screening of pathogens in the ticks was performed through real-time PCR. Ticks (n = 1849) were of mixed developmental stages: 76 larvae, 1295 nymphs, 426 adults and 52 undetermined. All analyzed ticks were considered negative for these pathogens since the CT-values were all below the detection limit for Bartonella spp. (1663 ticks), Francisella spp. (1849 ticks) and Toxoplasma gondii (1813 ticks). We assume that infections with these pathogens are caused by other transmission pathways within these regions of Sweden and the Åland islands, Finland.